The transition from vocational education and training to higher education in the German-speaking countries : chapter 3 - Schlögl, Peter [Verfasser] (My University, 2010)
"This brief comparison describes initiatives, mostly undertaken in the 1990s, to structurally link and define transition scenarios between VET at the upper-secondary level and HE programmes in Germany, Austria and Switzerland. The objective of this article is to analyse the fundamental educational policy conception of HE access, identify innovations made within the period of interest for this topic, and conduct a quantitative evaluation. Apart from considerable subject-related difficulties involved in such political projects, one formal aspect can be discerned in all three countries as particularly problematic, namely that the political stakeholders, educational practitioners and economic actors of these sectors are different in each case and that a culture of co-operation, trust and joint steering instruments cannot really be identified in this regard." (Autorenreferat, BIBB-Doku)
Keywords: G 2.5.3 Anschlussfähigkeit von Bildungsgängen; P 2.1.5 Fachhochschul- und Hochschulreife; T 1.5 International vergleichende Berufsbildungsforschung; I 2.1 Deutschland; I 2.2.1 Westeuropa; Durchlässigkeit im Bildungssystem; Hochschulzugang; Internationaler Vergleich; Bundesrepublik Deutschland; Österreich; Schweiz